Pengaruh Metode Pembelajaran Peer Teaching Terhadap Hasil Belajar Kognitif Siswa Pada Mata Pelajaran Matematika di Kelas V SDN 167 Pekanbaru - Khairunnisya Khairunnisya; Radhiyatul Fithri; Salman Salman (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the effect of peer teaching learning methods on students' cognitive learning outcomes in mathematics subjects in class V at SDN 167 Pekanbaru. The method used in this research is a quasi-experimental method with the dependent variable being student learning outcomes, the independent variable being the Peer Teaching method. Research was carried out through planning, action implementation, observation and evaluation stages. The subjects of this research were determined using purposive sampling, namely class Vb SDN 167 Pekanbaru, totaling 30 people. Data was collected using student activity observation sheets and knowledge tests. The collected data was analyzed using quantitative analysis. The results of the research show that the peer teaching learning method can influence the cognitive learning outcomes of class V students at SDN 167 Pekanbaru in Mathematics learning by 71.69%, namely in the high category G > 70%